Numerical analysis of effective mechanical properties of rubber-cord composites under finite strains. (1st November 2015) - Levin, V.A.; Zingerman, K.M.; Vershinin, A.V.; Yakovlev, M.Ya.
Abstract: In this article, a method and an algorithm are developed by which the effective mechanical properties of rubber-cord composites are numerically estimated, with the finite strains and low compressibility of rubber accounted for. The effective properties are derived in the form of a quadratic relation between the Green deformation tensor and the second Piola–Kirchhoff stress tensor. Numerical results obtained using implementation of this algorithm show good agreement with analytical formulas. The results of the numerical estimation of the effective mechanical properties of rubber-cord composite under finite strains are given in the article. The numerical analysis is carried out using the finite element method. Dependences of the effective modules on the elastic properties of cord and rubber and on the cord pitch are investigated for single-layer rubber-cord. Dependences of the effective modules on the cord angle are investigated for two-layer rubber-cord. Graphs of these dependences are given in the article.